Design, analysis, and performance evaluation of steam-CO2 reforming reactor for syngas production in GTL process - Park, Daeil; Lee, Changwook; Moon, Dong Ju; Kim, Taegyu (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Design and thermal-fluidic analysis of CH4 steam-CO2 reforming (SCR) reactor for gas to liquid-floating production storage and offloading (GTL-FPSO) is presented in this paper. The temperature distribution through the SCR reactor should be uniform in order to optimize the catalytic reforming reaction. The numerical analysis of heat, flow and catalytic reactions was used to design the SCR reactor. The kinetic constants for catalytic analysis were calculated from Arrhenius plot that was obtained by SCR experiments on Ni/Al2O3 pellet catalysts. The catalysts were prepared by impregnating Ni into commercial Al2O3 pellets. The reaction temperatures ranged from 1023 K to 1173 K. The CH4 and CO2 conversions increased with the temperature, while H-2/CO ratio of syngas decreased with the increase of temperature. And the metallic foam catalyst showed a higher CH4 conversion than a pellet catalyst. The commercial FLUENT code was used to predict the temperature distribution in the SCR reactor. It was shown that the performance of SCR reactor depends strongly on the temperature distribution through the catalysts. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: METALLIC FOAM CATALYST; SYNTHESIS GAS; PARTIAL OXIDATION; FPSO PROCESS; METHANE; DEPOSITION